Relation between self-concept and students alcohol drinking - José Vasconcelos-Raposo; Octávio V. Gonçalves; Carla M. Teixeira; Helder Miguel Fernandes (Desafio Singular, 2009)
This study examines the relation between multiple self-concept dimensions and alcohol consumption within the adolescent schooling. A sample of 642 students (263 boys and 379 girls) aged between 15 and 23 years completed the Self-Description Questionnaire II (SDQ II) and an alcohol drinking measure. Results reveal an absence of significant relationships between global self-esteem and alcohol consumption and a small relation, found only in the female, between alcoholic drinking and global self-concept, supporting the assumption that supports the low sensitivity and the consequent use of scarce global dimensions of the self. In contrast, there are significant relations between some specific dimensions of the self and alcohol consumption, whilst the correlation coefficients vary according to subject's gender, suggesting a cultural involvement based analysis.